Manajemen Pengembangan Pembelajaran Kitab Kuning - Nurul Hanani (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2017)
Kitab kuning viewed as theory and values contributor that followed al-Quran and Hadis Nabi as a background. In pesantren world, kitab kuning position are very strategic because it used as text book, references, and curriculum within pesantren education system. Aside from being religion procedure guideline,kitab kuning also functioned as universalreferences on responding every life challenge among pesantren people. Presevartion of learning method with kitab kuning in pesantren has been running constantly and culturally being special characteristic of pesantren. There is a few kitab kuning categorization which is based on its'characteristic, meaning content, serving proportion, writing creativity, and description appearance. The learning method of kitab kuning in salafiyah pesantren will not be separated from conventional traditional method use. These are few learning method we talking about; wetonan or bandongan, sorogan and hafalan (tahfidz) and munazharah (musyawarah/muzkarah). There is also learning evaluation in the learning method of kitab kuning.